Comparison of patients' diagnoses in a dermatology outpatient clinic during the COVID‐19 pandemic period and pre‐pandemic period. Issue 4 (26th December 2020) - Turkmen, Dursun; Altunisik, Nihal; Mantar, Irem; Durmaz, Imge; Sener, Serpil; Colak, Cemil
Abstract: Aim: In this study, we compared the current diagnoses of patients admitted to the dermatology outpatient clinic with the diagnoses during the non‐pandemic period, and we examined the effect of COVID‐19 on the patient profile. Methods: Diagnoses were compared by examining the patient files of the 3‐month period when the pandemic was influential in our country and the 2‐week non‐pandemic period corresponding to the same season a year ago. The outpatient diagnoses in the first month and the last month of the 3‐month pandemic period were also compared. Results: During the 3‐month pandemic process, the most common reasons for applying to the outpatient clinic were acne, urticaria, psoriasis, and allergic/irritant contact dermatitis. Urticaria, psoriasis, allergic/irritant contact dermatitis, scabies, liken planus, mycosis fungoides, zona zoster, recurrent aphthous stomatitis and polymorph light eruption were statistically more common in the pandemic period. Moreover, acne, other eczematous dermatities, verruca, androgenic alopecia, and melanocytic nevus diagnoses were found to decrease statistically during the pandemic period when compared with the non‐pandemic period. Conclusion: Unlike other studies, the present study evaluated the patient diagnoses during the pandemic period and the period a year before and discussed the possible reasons for the changes in patient profiles.